Development of Flipbook E-Modules to Enhance Science Literacy in the Living Things and Environment Topic - Enni Setyorini; Sukarmin Sukarmin; Harlita Harlita (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Scientific literacy is an essential competency in 21st-century education, particularly in vocational schools where students are expected to apply scientific knowledge in real-life and professional contexts. This study aimed to develop an interactive e-book module to enhance students' scientific literacy on the topic of Living Organisms and the Environment by integrating batik ecoprint as a contextual learning medium. The novelty of this research lies in positioning batik ecoprint not merely as a practical skill activity but as a systematic scientific context within digital-based vocational learning. The study employed a Research and Development approach using the 4-D model, consisting of the define, design, develop, and disseminate stages. The e-book flipbook module was validated by experts in content, media, language, and instructional design using the Content Validity Index (CVI). Its effectiveness was examined using a quasi-experimental one-group pre-test–post-test design across three Grade X vocational school classes. Data were analyzed using N-Gain. The results indicate that the developed e-book flipbook demonstrates high feasibility and effectively improves students' scientific literacy at moderate to high levels, with N-Gain values ranging from 0.63 to 0.77. These findings confirm the effectiveness of integrating local cultural contexts into vocational science learning.